2013
DOI: 10.1063/1.4817808
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of silver-dielectric-silver nanoshell for sensing applications

Abstract: In this paper, resonance light scattering (RLS) properties of a silver-dielectric-silver nanoshell, based on quasi-static approach and plasmon hybridization theory, are investigated. Scattering spectrum of silver-dielectric-silver nanoshell has two intense and clearly separated RLS peaks and provides a potential for biosensing based on surface plasmon resonance and surface-enhanced Raman scattering. The two RLS peaks in silver-dielectric-silver nanoshell are optimized by tuning the geometrical dimensions. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Figure 6 a shows that the scattering efficiency of silver–dielectric–gold nanoshell increases by increasing the surrounding medium function from to , where becomes intense quickly and increases slowly, unlike that of Figure 5 . The inset of scattering cross section is shown in Figure 6 a, where causes a distinct red-shift with increasing surrounding medium function [ 15 , 19 ]. Due to the dielectric screening with a high refractive index, the induced charge on the outer gold nanoshell surface decreases, and then the induced charge on the inner surface of the silver core follows.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 a shows that the scattering efficiency of silver–dielectric–gold nanoshell increases by increasing the surrounding medium function from to , where becomes intense quickly and increases slowly, unlike that of Figure 5 . The inset of scattering cross section is shown in Figure 6 a, where causes a distinct red-shift with increasing surrounding medium function [ 15 , 19 ]. Due to the dielectric screening with a high refractive index, the induced charge on the outer gold nanoshell surface decreases, and then the induced charge on the inner surface of the silver core follows.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Figure 7 b shows the local electric field focused in the middle dielectric layer, whereas the inner gold core and outer silver nanoshell are much weaker at wavelength 722 nm. There are different kinds of charges signed on the inner gold core and inner surface of the outer silver nanoshell, which attracts in mode [ 15 , 19 ]. The scattering efficiency can be well improved with the larger inner core radius , smaller middle dielectric layer function , and larger surrounding medium .…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that silver-dielectric-silver (SDS) nanoshell has three LSPR peaks in its scattering spectra and could be optimized for biomedical sensing. 10,11 However, the shortest wavelength peak is also very weak. If this peak could be enhanced, there will be three intense and separate LSPR peaks for multiplex sensing.…”
Section: Introductionmentioning
confidence: 97%
“…[12] Schiditabar et al have investigated the resonance light scattering properties of silver-dielectricsilver nanoshell based on quasi-static approach, and the results show that LSPR are optimized by tuning the geometrical dimensions. [13] Based on the light absorption spectra properties of a bimetallic multilayer nanoshell (silver-dielectricsilver, gold-dielectric-silver and silver-dielectric-gold), the results show that relatively small thickness of outer silver shell and large dielectric constants of middle dielectric layer of gold-dielectric-silver nanoshell are suitable to obtain the triple plasmon resonance. [14] Recently, the optical properties of nanotube have also been widely investigated and applied in biological tissues, nanosensors, optical devices, optical data storage and some regions.…”
Section: Introductionmentioning
confidence: 99%